Process induced alignment of carbon nanotube decreases longitudinal thermal conductivity of Al2O3 based porous composites. Issue 15 (15th October 2019) - Ariharan, S.; Wangaskar, Bhimashankar; Xavier, Vincent; Venkateswaran, T.; Balani, Kantesh
Abstract: Alumina (Al2 O3 ) based porous composites, reinforced with zirconia (ZrO2 ), 3 and 8 mol% Y2 O3 stabilized ZrO2 (YSZ) and 4 wt% carbon nanotube (CNT) are processed via spark plasma sintering. The normalized linear shrinkage during sintering process of Al2 O3 -based composite shows minimum value (19.2–20.4%) for CNT reinforced composites at the temperature between 1650 °C and 575 °C. Further, the combined effect of porosity, phase-content and its crystallite size in sintered Al2 O3 -based porous composite have elicited lowest thermal conductivity of 1.2 Wm −1 K −1 (Al2 O3 -8YSZ composite) at 900 °C. Despite high thermal conductivity of CNT (∼3000 Wm −1 K −1 ), only a marginal thermal conductivity increase (∼1.4 times) to 7.3–13.4 Wm −1 K −1 was observed for CNT reinforced composite along the longitudinal direction at 25 °C. The conventional models overestimated the thermal conductivity of CNT reinforced composites by up to ∼6.7 times, which include the crystallite size, porosity, and interfacial thermal resistance of Al2 O3, YSZ and, CNT. But, incorporation of a new process induced CNT-alignment factor, the estimated thermal conductivity (of <6.6 Wm −1 K −1 ) closely matched with the experimental values. Moreover, the high thermal conductivity (<76.1 Wm −1 K −1 ) of the CNT reinforced porous composites along transverse direction confirms the process induced alignment of CNT in the spark plasma sintered composites.